2005
DOI: 10.1016/j.clpt.2004.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical consequences of cytochrome P450 2C9 polymorphisms

Abstract: The gene coding for the cytochrome P450 (CYP) enzyme 2C9 (CYP2C9) carries numerous inherited polymorphisms. Those coding for R144C (*2) and I359L (*3) amino acid substitutions have both significant functional effects and appreciable high population frequencies, and their in vivo consequences have been studied in humans with regard to drug metabolism. This review summarizes present knowledge about the pharmacokinetics, drug responses, and outcomes of clinical studies in individuals with different CYP2C9 genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
277
2
8

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(291 citation statements)
references
References 124 publications
4
277
2
8
Order By: Relevance
“…To date, more than 50 variants in the CYP2C9 gene have been described (Allele Nomenclature Committee home page: http://www.imm.ki.se/CYPalleles), of which two single-nucleotide polymorphisms (SNPs), CYP2C9*2 (R144C) and CYP2C9*3 (I359L), have been well verified in relation to the wild-type allele CYP2C9*1. No Asians so far studied have the CYP2C9*2 allele (Kimura et al 1998;Takahashi et al 2003;Kirchheiner and Brockmoller 2005). Previous studies have demonstrated that the warfarin 7-hydroxylase activity of the CYP2C9*3 variant allele is approximately 10-fold lower than that of CYP2C9*1 in in vitro analysis (Lee et al 2002) and that carriers of the variant allele required a lower maintenance dose of warfarin (Takahashi et al 2003;Kirchheiner and Brockmoller 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 50 variants in the CYP2C9 gene have been described (Allele Nomenclature Committee home page: http://www.imm.ki.se/CYPalleles), of which two single-nucleotide polymorphisms (SNPs), CYP2C9*2 (R144C) and CYP2C9*3 (I359L), have been well verified in relation to the wild-type allele CYP2C9*1. No Asians so far studied have the CYP2C9*2 allele (Kimura et al 1998;Takahashi et al 2003;Kirchheiner and Brockmoller 2005). Previous studies have demonstrated that the warfarin 7-hydroxylase activity of the CYP2C9*3 variant allele is approximately 10-fold lower than that of CYP2C9*1 in in vitro analysis (Lee et al 2002) and that carriers of the variant allele required a lower maintenance dose of warfarin (Takahashi et al 2003;Kirchheiner and Brockmoller 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes display polymorphism and their prevalence varies among different populations. [1][2][3] In particular, the polymorphic enzyme CYP2C9 is the most abundant of the CYP2C enzymes, 4 and it influences the metabolism of about 10-20% of therapeutically important drugs, 5 some with a narrow therapeutic index. A high number of genetic polymorphisms associated with wide interindividual variability in the hepatic metabolism of target drugs have been described in the regulatory and coding regions of CYP2C9 gene; 6 however, only two coding variants, CYP2C9*2 (C430T) and CYP2C9*3 (A1075C), with functional consequences are common.…”
Section: Introductionmentioning
confidence: 99%
“…50 An additional ramification of decreased activity of the CYP2C9*2 and CYP2C9*3 alleles can include an increase in the concentrations of NSAIDs in patients, inadvertently manifesting itself as an acute upper gastrointestinal bleeding. 56 This understanding helped initiate a prospective study seeking to determine whether the frequency of the CYP2C9*3 allele would be overrepresented among patients treated with non-aspirin NSAIDs in comparison with the frequency of the CYP2C9*3 allele for patients on aspirin would be comparable to the general population's frequency. 57 The non-aspirin NSAID group, in addition to ibuprofen, included ketoprofen, diclofenac, piroxicam, meloxicam, tenoxicam and rofecoxib.…”
Section: Propionic Acid Derivativesmentioning
confidence: 99%